Faktor-Faktor Yang Mempengaruhi Pelanggan Menunggak Rekening Listrik Pada PLN Sub-Rayon Sentebang - Dedi Hariyanto; Subhan A (Universitas Muhammadiyah Pontianak, 2015)
This research is using survey. Populations used are all customers of PT. PLN (Persero) Sub Rayon Sentebang ever in arrears to pay the electricity bill, with a sample of 100 people who use techniques Probability Sampling type of stratified sampling proportional sample criteria in this study are customers aged> 20 years, whether married or not married and customer ever dives at least 2 months delinquent. This study using factor analysis. The results showed that the Factors Affecting Customer DelinquentElectricity Account In. PLN (Persero) Sub Rayon Sentebang is the payment process is complicated, quality distribution of electricity that is not good, quality of service disruption poor, low income customers, Deliberate customers delay payments, attitude PLN officers unfavorable, fee late charges are low, the payment system is not good, often delay the payment of electricity bills and lack of good quality KWH meter PLN.